Is Obesity Associated With an Increased Risk of Complications After Surgical Management of Acetabulum and Pelvis Fractures? A Systematic Review. (April 2021) - Mittwede, Peter N.; Gibbs, Christopher M.; Ahn, Jaimo; Bergin, Patrick F.; Tarkin, Ivan S.
Abstract : Background: When considering surgical fixation of acetabulum and pelvis fractures in patients with obesity, a thorough understanding of the risks of potential complications is important. We performed a systematic review to evaluate whether obesity is associated with an increased risk of complications after surgical management of acetabulum and pelvis fractures. Methods: We searched PubMed/MEDLINE, EMBASE, and the Cochrane Library for studies published through December 2020 that reported the effect of increased body mass index (BMI) or obesity on the risk of complications after surgical treatment of acetabulum and pelvis fractures. Results: Fifteen studies were included. Eight of the 11 studies that included infection or wound complication as end points found that increased BMI or some degree of obesity was a significant risk factor for these complications. Two studies found that obesity was significantly associated with loss of reduction. Other complications that were assessed in a few studies each included venous thromboembolism, nerve palsy, heterotopic ossification, general systemic complications, and revision surgery, but obesity was not clearly associated with those outcomes. Conclusions: Obesity (or elevated BMI) was associated with an increased risk of complications—infection being the most commonly reported—after surgical management of acetabulum and pelvis fractures, which suggests the need for increased perioperative vigilance.